STRATEGI MENGATASI KETERGANTUNGAN PEMERINTAH DAERAH KABUPATEN KONAWE UTARA TERHADAP DANA PERIMBANGAN PUSAT - La Ode Agus Said (Universitas Halu Oleo, 2018)
The purpose of this paper is to strategy to overcome the level of dependence of regional governments on the balance funds in Konawe Utara District and analyze the level of dependence of the North Konawe District government on balance funds. The research method used is a qualitative research method using descriptive analysis method. Through this process, it is expected to emerge a new hypothetical proposition through the interpretation of interactions between attributes and propositions which are then used to construct categories and provide explanations of the phenomena under study. Data collection techniques are in-depth interviews and document studies. Based on the results of the study, the strategy of the North Konawe District Government in managing the level of dependence on balancing funds in supporting the Regional Expenditure Budget was carried out with 2 (two) patterns: 1) Intensification, namely the North Konawe District Government to optimize Local Revenue by optimizing existing regional tax sources and regional levies; 2) Extensification is to control the level of dependence on balance funds by increasing the revenue of the District of North Konawe by placing more emphasis on expanding new sources of income, namely by developing retribution on fees from the development of market services, parking fees and other fees. The level of regional dependence on balancing funds consisting of Revenue Sharing Funds, General Allocation Funds and Special Allocation Funds is 78.90%, which indicates that the balancing funds contribute significantly to the district's income Konawe Utara. This means that the level of dependence of regional governments on balancing funds is still quite high, which can be reduced by optimizing other sources of income. Keywords: Strategy, Local Government, Balancing Fund